Electrodeposition and properties of Ni–B/SiC nanocomposite coatings. (1st February 2019) - Li, B. S.; Huan, Y. X.; Luo, H.; Zhang, W. W.
ABSTRACT: Ni–B/SiC composite coatings were electrodeposited using trimethylamine borane as a boron source. The effects of bath composition and operating parameters on the microstructure and properties of the composite coatings were investigated. The results show that Ni–B/SiC composite coating exhibits uniform structure with a desirable interface. Incorporation of SiC particles led to a signiﬁcant increase in hardness. Both boron and SiC content in the coating increases initially and then decreases as the current density increased. Incorporation of inert SiC particles also enhanced their corrosion resistance, which attributed to the dense structure, barrier effect and the reduction in the active surface area of Ni–B matrix. XPS analysis indicated that the as-deposited coating contains metallic nickel, oxide or hydroxide nickel, and the SiC particles. Owing to dispersion hardening of the added SiC particles and the reduction in the active surface area of Ni–B matrix, Ni–B/SiC composite coating shows superior anti-corrosion and wear resistance.